2018
DOI: 10.1007/s10238-018-0517-2
|View full text |Cite
|
Sign up to set email alerts
|

A clinical analysis of 114 cases of sarcomatoid carcinoma of the lung

Abstract: The aim was to investigate the clinicopathological characteristics, diagnosis, and prognosis of sarcomatoid carcinoma of the lung. We reviewed 114 cases of sarcomatoid carcinoma of the lung in patients that were admitted to the First Affiliated Hospital of Zhengzhou University and Anyang Tumor Hospital from January 2009 to March 2018. We analyzed the clinical characteristics, immunohistochemical profiles, treatments, and overall survival of the patients. The patient population included 88 men and 26 women. Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 21 publications
4
20
3
Order By: Relevance
“…Surgery remains the primary treatment approach for PSC, and surgery was performed in most of our patients (91.2%). In line with previous reports (20,21), our study verified the prolongation of survival with surgical treatment compared with nonsurgical treatment (MST, 23.0 vs. 11.0 months, P=0.016). In terms of adjuvant therapy, however, our study found no survival benefit from adjuvant therapy after surgical resection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Surgery remains the primary treatment approach for PSC, and surgery was performed in most of our patients (91.2%). In line with previous reports (20,21), our study verified the prolongation of survival with surgical treatment compared with nonsurgical treatment (MST, 23.0 vs. 11.0 months, P=0.016). In terms of adjuvant therapy, however, our study found no survival benefit from adjuvant therapy after surgical resection.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with the other studies (6,(18)(19)(20), our study reported a relatively lower rate of metastatic disease (6.5%) at the initial diagnosis, which may be due to the fact that some metastatic patients were identified in district hospitals were not referred to our hospital. The total cohort had an MST of 22.0 months; however, prior published series reported a relatively short MST ranging from 3.5 to 19.1 months (5,6,(18)(19)(20)(21)(22)(23). This may be largely due to the higher proportions of early-stage and surgically resected patients in our cohort.…”
Section: Discussioncontrasting
confidence: 83%
“…3 Patients with pN0 disease had a high rate of vascular invasion (57.1%), indicating that distant metastases may often occur in the early stage; this phenomenon might explain why N stage does not affect prognosis. 12,23,28,29 The presenting complications of PSC are similar to those of other lung cancers. In addition, tumor metastasis often includes various involved organs, such as the lung, adrenal glands, pleura, brain, bone, or liver, but may also include unusual anatomic sites, such as subdiaphragmatic nodes, kidney, peritoneum, pancreas, skin, and right ventricle.…”
Section: Clinical Featuresmentioning
confidence: 89%
“…Palliative anti-tumor therapy is often the best choice to prolong OS. 12 Drug resistance can occur with platinum plus pemetrexed chemotherapy in a short time, resulting in tumor recurrence. 52 The efficacy of combined adriamycin and ifosfamide chemotherapy to treat patients with metastatic PSC has been limited.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation